Analysis of the Socio-Political Dimension of Madrasah Education Program in Bangsamoro Autonomous Region in Muslim Mindanao - Andang-Alaiden, Esmaida; Pantao, Jovar G.; Lañojan, Rhumer S.; Aguja, Mario G. (Pancasila International Journal of Applied Social Science, 2025)
Madrasah education has played a crucial role in the educational landscape of Mindanao, Philippines, particularly for Muslim communities. Traditional Madaris provide religious instruction and support for Muslim students' cultural identity. The government has been supporting the integration of Madrasah into the mainstream through different legislations, policies, peace agreements and educational reforms. Yet, challenges still exist in providing and satisfying the academic needs of Muslim learners, especially in the Bangsamoro Autonomous Region of Muslim Mindanao. This study explored the social and political factors shaping the Madrasah educational System in the communities surrounding the Ligawasan Marsh within the Bangsamoro Autonomous Region in Muslim Mindanao. It offered recommendations to transform the Madrasah educational system. Findings revealed that social dimensions in shaping the implementation of the Traditional Madrasah include the selective implementation of the Refined Standard Madrasah Curriculum, increasing need for a balanced education, gender disparity in Madrasah attendance, decreasing trend in the learning outcomes, multilingual instruction and the unpredictable vulnerability of these Madaris to extreme and violent ideologies. On the other hand, political dimensions consist of increasing efforts in reforming Madrasah Education, changing political leadership and landscape, absence of a standardised practice for Madrasah teachers and introducing new administrative procedures and regulations. This paper recommends a comprehensive curriculum to include peace concepts, continuing education for teachers, strategic & complementary partnerships among stakeholders of Madrasah education, monitoring and evaluation mechanisms for the learning outcomes and policy support, advocacy & communication. This is to ensure inclusive and culturally responsive policies for a sustainable future of the Muslim children in Ligawasan and areas where there are Bangsamoro learners.